Hubungan Indeks Massa Tubuh (IMT) Dengan Anemia Pada Ibu Hamil Trimester I Di Puskesmas Sekapuk Ujung Pangkah Gresik - lailah, Alfu; Mudlikah, Siti (Universitas Muhammadiyah Gresik, 2024)
Background: Pregnancy anemia occurs due to iron deficiency, vitamin B12 deficiency, folic acid deficiency, infectious diseases, congenital factors and bleeding. Factors of pregnancy anemia are a lack of body mass index in pregnant women, checking body mass index before pregnancy to determine the presence of anemia in pregnant women. The aim of the research was to determine the relationship between body mass index and pregnancy anemia at the Sekapuk Ujung Pangkah Gresik health center. Methods: observational analysis, cross sectional approach, the population of first trimester pregnant women was 48 people. Number of samples using total sampling technique. Body mass index (BMI) data is obtained from measurements of body height and weight. Anemia data was obtained from the pregnant women's cohort book. And the analytical test uses the Spearman rank test. Results: The most anemic pregnant women in terms of body mass index are: Underweight, 13 people (27.1%), overweight, 12 people (25%), ideal, 10 people (20.8%) and obesity, 0%. Meanwhile, pregnant women who were not anemic were: 8 people ideal (16.7%), 4 people overweight (8.3%), 1 person obese (2.1%) and 0% underweight. There is a relationship between Body Mass Index and Anemia in pregnant women at the Sekapuk Ujung Pangkah Gresik Community Health Center with a p-value of 0.04 (p-value <0.05). Conclusion: There was a relationship between body mass index and anemia in pregnant women at the Sekapuk Ujung Pangkah Gresik Community Health Center.